Strategy mapping and introducing the Health System Reform Plan: An Iranian social responsibility-based approach - janbazi, shahriar; Rabiee Mandejin, Mohammad Reza; Eslambulchi, Alireza; Bahadori monfared, Ayad (Social Determinants of Health, 2019)
Background: The main function of the strategy map is to determine the relationship between cause and effect among the strategic objectives, dimensions, and components of an organization, a large project or plan in which programs can be implemented effectively. The current study aimed to map strategy and introduce the health system reform plan using an Iranian social responsibility-based approach. Methods: The current study was a qualitative and applied one using the Balanced Scorecard (BSC) principles and the Comprehensive Evaluation Model for Health System Reform Plan in Iran (CEHSRP-IR) model in 2019. the views of 17 experts were selected in management and health issues based on purposive non-random sampling, using Delphi technique paired comparisons, common techniques in strategy mapping, and SPSS and EXPERT CHOICE software, the strategy map of the health system reform plan was designed in Iran. Results: After elaborating on the fundamental aspects of this research, setting the strategic goals, dimensions, and components, as well as determining the relative weight of the components and dimensions and then prioritizing them, explained their optimal relationships to achieve strategic goals. Finally, using VISIO software, a strategy for the health system reform plan was designed and presented concerning social responsibilities. The present study resulted in designing a strategy map of the health system reform plan in Iran based on 5 dimensions of financial, social responsibility, learning and growth, clients, internal processes, 17 components, and 25 connections. Conclusion: The current strategy map can be sufficiently comprehensive to effectively implement nationally at various organizational and implementing units’ levels of the health system reform plan in Iran.